Capacidade fitorremediadora de espécies florestais aos herbicidas Atrazine e 2,4-D em dois tipos de solos - Heemann, Tagliane Puhl (2017)
With the intensification of agricultural production, it has as a consequence the increase in chemical control of weeds, causing damage to the environment and to humans, for contaminating the ecosystem. Faced with this reality, measures to prevent or remedy the negative effect of the herbicides have been necessary, especially when it comes to those with high mobility in the environment. Between the herbicides that have high mobility in the environment are the 2,4-D and atrazine. The objective of this work was to evaluate the potential of three forest species as phytoremediation of atrazine and 2,4-D leached in two soils of different textures, using the technique of bioassay. The experiment was conducted in a greenhouse in a randomized block design, in factorial 2x3x3, with four replications, corresponding to two soils (Red-Yellow Latossol (LVA), clay texture and Quartzarenic Neossol (RQ), sandy texture), three solutions of herbicides (witness, 2,4-D and atrazine) and three forest species embaúba (Cecropia hololeuca), eucalyptus (Eucalyptus grandis x Eucalyptus urophylla) and jatobá (Hymenea coubaril). We evaluated the stem diameter (DC), plant height (AP), number of leaves (NF), chlorophyll a and b (Cl and Clb), phytotoxicity (%), wet mass and dry matter of aerial part (MUA and MSA) and dry roots (MSR). For verification of remediating capacity of species has been sowing the cucumber, as indicator species the presence of herbicides in soils. For comparison of averages, we used the Tukey test at 5% probability. The eucalyptus was the species that showed greater tolerance to the action of herbicides. The prior cultivation of tree species was positive about the reduction of waste of atrazine and 2,4-D in most treatment, except for the species jatobá cultivated in soil LVA. Thus, the species evaluated showed potential for more in depth studies of phytoremediation mainly for the species coffea and jatobá for contamined size with 2,4-D and atrazine, respectively and eucalyptus for both.